Keanekaragaman Morfologis Sukun [Artocarpus altilis (Park.) Fosberg. var. non-seminiferus] Di Daerah Banyumas - Rizkyana, Risna; unsoed, sukarsa; Widodo, Pudji; Palupi, Dian (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Breadfruit [Artocarpus altilis (Park.) Fosberg] is a plant that have different morphological variations in each region. The Banyumas area is an area that is very suitable for the growth of breadfruit. This study was aimed to determine the diversity of breadfruit plants based on their morphological characteristics. This research was conducted using a survey method, then the data were analyzed descriptively. The research variable was the morphological characteristics of the breadfruit plant, the parameters were the morphological of the canopy, buttress roots, stems, leaves, flowers, and fruits. The results showed that the morphological variations of breadfruit were found in the shape of the canopy varies, namely broad pyramid, pyramid, ovoid, round, and irregular, some have buttress roots and none, fruit shape varies, namely round and oval. Leaf blade length varies between 26-56 cm, leaf blade width varies between 20-45 cm, leaf stalk length varies between 3-6 cm, leaf shape is ovoid, upper leaf surface is smooth, lower leaf surface is rough, leaf edge incised, the tip of the leaf is tapered, the base of the leaf is wedged, the color of the leaf is dark green. Male flower length varies between 9-17 cm, male flower color varies, namely light green and brownish, male flower shape resembles a club, female flower diameter varies between 5-6 cm, female flower shape is round, female flower color is light green. Fruit weight varies between 450-1250 g, fruit diameter varies between 9-18 cm, fruit skin color is green, flesh color is white to yellowish white, flesh texture is smooth, fruit skin pattern is polygonal, and seeds are round, black.